Gordon Valentine Manley and his contribution to the study of climate change: a review of his life and work - Endfield, Georgina H.; Veale, Lucy; Hall, Alexander (Wiley, 2015)
British climatologist and geographer, Gordon Manley (1902–1980), is perhaps best known for his pioneering work on climate variability in the UK, for establishing the Central England Temperature series and, for his pivotal role in demonstrating the powerful relationship between climate, weather, and culture in post-World War II Britain. Yet Manley made many contributions, both professional and popular, to climate change debates in the twentieth century, where climate change is broadly understood to be changes over a range of temporal and spatial scales rather than anthropogenic warming per se. This review first establishes how Manley's work, including that on snow and ice, was influenced by key figures in debates over climatic amelioration around the North Atlantic between 1920s and 1950s. His research exploring historical climate variability in the UK using documentary sources is then discussed. His perspectives on the relationship between climate changes and cultural history are reviewed, paying particular attention to his interpretation of this relationship as it played out in the UK. Throughout, the review aims to show Manley to be a fieldworker and an empiricist and reveals how he remained committed to rigorous scientific investigation despite changing trends within his academic discipline.